2002
DOI: 10.1046/j.1365-8711.2002.05071.x
|View full text |Cite
|
Sign up to set email alerts
|

Pair annihilation and radio emission from galactic jet sources: the case of Nova Muscae

Abstract: In the hard X‐ray spectra of some X‐ray binaries line features at around 500 keV are detected. We interpret these as arising from pair annihilation in relativistic outflows leading to a significant Doppler shift of the frequencies of the lines. We show how this can be used to accurately determine the bulk velocity and orientation to the line of sight of the outflows. Constraints on the energy requirements of such outflows are also derived. Furthermore, we show that a small fraction of pairs escaping the annihi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The topological self-screening of u in p The process does not yield the anticipated pion  0 which would indeed have only moderate mass since in the meson, the circulations of linked quark and antiquark pair cancel apart from the lag-phase accrued along their opposite pitches. Thus, the violation of color confinement would require extraordinarily high-energy surroundings to provide the asymptotic freedom [55] for quark-gluon plasma, or the violation of baryon number conservation would require a blazing transformation [56,57].…”
Section: Multiple Actionsmentioning
confidence: 99%
“…The topological self-screening of u in p The process does not yield the anticipated pion  0 which would indeed have only moderate mass since in the meson, the circulations of linked quark and antiquark pair cancel apart from the lag-phase accrued along their opposite pitches. Thus, the violation of color confinement would require extraordinarily high-energy surroundings to provide the asymptotic freedom [55] for quark-gluon plasma, or the violation of baryon number conservation would require a blazing transformation [56,57].…”
Section: Multiple Actionsmentioning
confidence: 99%
“…Indeed the discrete character of nature is reflected in mult iplicity at all levels of its hierarchical organization [53]. Ad mittedly, the proton seems immortal in our hands, but the baryon conservation is at stake when matter and quanta of radiation as stoichiometric reactants are drawn in jaws at galactic centers that jet out leptons and γ-rays [54][55][56]. The photon is an apparent ingredient of chemical reactions, but it is the element of any other change of state as well.…”
Section: Discussionmentioning
confidence: 99%
“…The reader can find it in the quoted literature. Suffice it to mention that pair formation via magnetic reconnections has been recently assessed by [Dal Pino et al, 2010], that pair annihilations in neutron-star jet sources have been first reported by [Kaiser & Hannikainen, 2002], that functional regularities in micro-quasars and quasars are described in [Körding et al, 2006[Körding et al, , 2008, and that earlier interpretations of similar kinds of the jet phenomenon were given by [Phil Morrison, 1981], and by [Peter Scheuer, 1996]. Finally, if the CEs of the AGN are BDs rather than BHs, the rare, gigantic, supersoft X-ray outbursts reported by [Komossa, 2005] may have to be re-interpreted as caused by innermost stars on perturbed orbits colliding with the heavy innermost disk of their galaxy.…”
Section: How To Make Jets?mentioning
confidence: 99%